Pelaksanaan TQM dalam Syarikat Pengilang Logam: Kajian Kes - Ahmad @ Mohamad, Md Fauzi; Ismail, Muhammad Hazim; Abdul Rahman, Nor Aida; Ahmad Nur Aizat Ahmad (Research in Management of Technology and Business, 2022)
Today’s rapidly changing business world demands for continuous improvement through incorporating total quality management (TQM). TQM is important for a successful implementation. This research was conducted with the aimed to identify the critical success factor of total quality management (TQM) implementation in a metal stamping manufacturing company where ABC Sdn Bhd was chosen as the case study. Based on the findings, factors of TQM implementation are management commitment and leadership; continuous improvement; total customer satisfaction; employee involvement; training; communication and teamwork. Management commitment and leadership in TQM implementation was placed at first ranking. SWOT analysis based on the TQM implementation also being addressed based on the feedback received from the interview session with company representative. Thus, this study capable to further develop the understanding on how TQM is put into practice especially from the standpoint of a manufacturing firm and the challenges that business must deal for a successful TQM implementation.